Protected areas, conservation and resource capacity: Historical lessons for conservation from Western Australia’s South Dandalup Reserve - Calver, M.; Wardell-Johnson, Grant (Royal Zoological Society of New South Wales, 2016)
Impacts on the forested bioregions of south-western Australia have, since first European settlement in 1826, been extensive and dramatic. Large-scale land clearing removed over two-thirds of the vegetation for agriculture and urbanisation. Other significant threats to the biota include: changed fire regimes; exotic predators, diseases and herbivores; and drought and climate change. Conservation reserves in the region were originally chosen on aesthetic appeal, often aligning poorly to modern CAR (comprehensive, adequate and representative) criteria aspiring to conservation of at least 10% of each bioregion. The entire period of European occupation of the region has been characterised by the need to balance different land uses within a changing political context, broadening in recent years to incorporate indigenous culture and heritage. Thus much may be gained by a historical perspective grounding contemporary policy in an understanding of the successes and failures of the past. Here, we consider the historical development of the unique perspectives from forestry, agriculture and conservation through the late 19th and early 20th centuries, before assessing their interplay with newer concerns. This experience illustrates that society can design management systems to conserve biodiversity and ensure long-term sustainable use of renewable resources, but that the political will is often lacking.